Investigation Into The Quality Of Service(QOS) Requirements In Networked Multimedia Systems - Manimegalai , Parry (2005)
The main objective of this research work to develop a congestion avoidance mechanism by which Quality of Service can be achieved in networked multimedia systems. In this work, a NS-2 network simulator was used as a tool for the solution development. To select a suitable network simulator to be used in the congestion avoidance mechanism development, an analysis of network simulators was conducted prior system development.